"Change in schools it's more like sort of turning an oil tanker": Creating readiness for Health Promoting Schools. Issue 3 (1st June 2015) - Gardner, Belinda; Ollis, Debbie
Abstract : Purpose: – The purpose of this paper is to add to the evidence of best practice in the implementation of the Health Promoting Schools (HPS) framework by examining the process of creating readiness for change in a large international school in South-East Asia. Using a settings-based approach and guided by readiness for change theory the data collected reflects which factors were most influential in the decision of the leadership team (LT) to adopt a comprehensive HPS model. It follows the process of creating readiness in the early stages of adopting a HPS approach and captures the critical factors effecting leader's beliefs and support for the program. Design/methodology/approach: – This research is a case study of a large pre-K-12 international school in South-East Asia with over 1, 800 students. A mixed methods qualitative approach is used including semi-structured interviews and document analysis. The participants are the 12 members of the LT. Findings: – Readiness for change was established in the LT who adopted a HPS approach. That is, they adopted a comprehensive model to address health-related priorities in the school and changed the school's mission and accountability processes to specifically include health. Uncovering the reasons why the LT supported this change was the primary focus of this research. Building the motivation to change involved establishing a number of key beliefs three of which were influential in bringing about readiness for change in this case study. These included the belief that leadership support existed for the proposed change, a belief that there was a need for change with a clear discrepancy in the present and preferred operations in relation to addressing the health issues of the school and the belief that HPS was the appropriate solution to address this discrepancy. Research limitations/implications: – Adopting a HPS approach is the first phase of implementation. Long-term research may show if the integrity of the chosen model is maintained as implementation continues. The belief construct of valence, that is, the belief that the change will benefit the change recipient, was not reliably assessed in this research. Further research needs to be conducted to understand how this construct is interpreted in the school setting. The belief construct of valence was not reliably assessed in this research. Further research needs to be done to understand how this construct fits in the school setting. Practical implications: – This paper provides a promising example of how health can be integrated into the school's Mission and Strategic Learning Plan. The example presented here may provide strategies for others working in the field of HPS. Originality/value: – Creating readiness is an often over-looked stage of building sustainable change. International schools cater to more than three million students are a rarely researched in regards to health education. It is predicted that the numbers of students in international schools will grow to more than six million in the next ten years.